Forensic Toxicological Analysis of Ketamine and Norketamine in Fingers and Toenails using LC-QTOF-MS - Bansod, Nandini (Asian Journal of Pharmaceutics (AJP), 2025)
Background: Human nails are primarily composed of keratin, a fibrous protein. As nails grow, drugs that have been misused can become embedded in the keratin fibers, allowing detection even months after use. This prolonged retention has led to increased interest in utilizing keratinized matrices for both forensic and therapeutic purposes. Unlike traditional biological samples such as blood and urine, which have shorter detection windows, keratinized matrices can preserve evidence of repeated drug exposure for extended periods. Materials and Methods: This study analyzes nail clippings from five individuals with documented ketamine (KET) misuse. Before liquid chromatography-mass spectrometric analysis, the samples underwent a series of preparatory steps, including decontamination, hydrolysis in 1 M sodium hydroxide at 90°C for one hour with sonication, extraction using ethyl acetate, and reconstitution in methanol. Results: Calibration curves were created using reference standards, covering KET concentrations from 0.20 ng/mg to 16 ng/mg and norketamine (NKT) concentrations from 0.30 ng/mg to 16 ng/mg. The limits of quantification and detection for KET in spiked nail clippings were found to be 0.2 ng/mg and 0.05 ng/mg, respectively. For NKT, the respective values were 0.07 ng/mg and 0.15 ng/mg. Conclusion: This study presents a targeted analytical method for detecting KET and its metabolite, NKT, in human nails. The proposed approach could be valuable for applications such as monitoring drug misuse, investigating drug-facilitated crimes, and assessing cases of medical negligence.